Training patterns and negative health outcomes in triathlon: longitudinal observations across a full competitive season - Main, L. C.; Landers, G. J.; Grove, J. R.; Dawson, B.; Goodman, C. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: Despite heavy training requirements, triathlon is a sport that is rapidly increasing in popularity. Yet, there is limited research detailing the relationship between training, the incidence of injuries and illness, psychological stress, overtraining and athlete burnout amongst triathletes. Six hypotheses relating inter-individual differences to training factors were generated to evaluate change in self-reported measures of these negative health outcomes over a training year. METHODS: Thirty, well-trained, triathletes (males n=20: age=27.1±9.1 years and females n=10: age=27.4±6.6 years) from a local triathlon club participated in this study. The study commenced during pre-season training, and involved weekly monitoring of each athlete until the end of the competitive season 45 weeks later. Linear Mixed Modelling was used for the analysis. RESULTS: Signs and symptoms of injury and illness (SAS) were significantly associated with increases in training factors (P=0.05); however, greatest impact on SAS was produced by psychological stressors (P=0.001). Common symptoms of overtraining were significantly affected by increases in exposure to both training and psychological stressors (P=0.05). Mood disturbance was not significantly affected by training factors (P>0.05) but rather increases in psychological stressors (P=0.001). Finally, each of the three athlete burnout subscales were significantly affected by both psychological (P=0.001) stressors as well as varying combinations of training factors (P=0.05). CONCLUSIONS: Exposure to stressors (either training or psychological) had significant effects on all negative health outcomes assessed.